STUDY ON INFLUENCE OF COVID-19 ONCORPORATE EFFECTIVENESS OF BANKING SECTOR - Rani, Usha; Shrivastava, Manish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
To combat a pandemic like CoVD-19, the Indian government has proposed a nationwide lockout beginning on March 24, 2020, and continuing until May 3, 2020. In order to prevent further loss of life, the Indian government must implement a lockout. Multiple parts of our economy will be badly impacted. The banking sector provides crucial support to the Indian economy. This piece is an effort to quantify the monetary losses sustained by financial institutions as a result of the lockdown that would be necessary in the event of a pandemic similar to covid-19. The sample size for the study includes 16 different deposit money banks across India. An indicative sample of four financial institutions was chosen. A total of 250 participants were randomly selected from the whole study population. A structured questionnaire was used to collect the information, and they were handed out to people individually. Frequency, mean, and standard deviation calculations were used to analyze the data and provide insight into the research issues. The study found that the covid-19 lockdown had a statistically significant detrimental influence on banking sector corporate effectiveness.